(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2023)
Assessment of water quality has been an important issue nowadays as the available water supply is severely polluted and can be the cause of waterborne diseases like cholera, diarrhea and dysentery. Solar disinfection (SODIS) is an efficient, low technology and cost-effective method for inactivation of pathogenic microorganisms in low-income communities where clean drinking water is limited or absent. The study was designed to assess the information about sanitation behavior at the household level using a structured questionnaire and to provide cost-effective method for its treatment. The result of the bacteriological analysis shows that all the water samples were found to harbour coliforms organisms in numbers greater than the required WHO/FAO/NSDWQ standards. The isolated organisms were identified to be Enterobacter aerogenes, species. SODIS was proven to be a more environmentally friendly and low-cost method to disinfect water against the conventional methods of water treatment that require high technology and it is time-consuming. In addition, the chemical used in the treatment process might be toxic. Providing the community with simple water treatment techniques using the SODIS method, and intensive health education and sanitation practices for the community are highly recommended.